Formative Assessment in Scaffolded Learning: Enhancing Students’ Autonomy in Written Communication Skills - Saputri, Vike Aprilianin Marwintaria; Setiyadi, Ag. Bambang; Haenilah, Een Yayah; Siregar, Rabiyatul Adawiyah; Raja, Patuan; Hariri, Hasan; Sunyono, Sunyono (Journal of Language and Literature Studies, 2026)
Students’ autonomy in written communication is a key component of 21st-century learning, enabling learners to express ideas effectively and take responsibility for their learning. However, many students still face difficulties in writing, particularly in organizing ideas and developing independence. Therefore, integrating formative assessment within a scaffolded learning framework is considered a promising approach to address these challenges. This study aims to investigate the role of formative assessment in scaffolded learning in enhancing students’ autonomy in written communication skills. This study employed a mixed-method design involving 22 second-semester students of the Buddhist Communication Science Department. The instruments included a writing test, a learner autonomy questionnaire, and interviews. Quantitative data were analyzed using a paired sample t-test, while qualitative data were analyzed descriptively. The results showed a significant improvement in students’ writing performance, with the mean score increasing from 50.5 (pre-test) to 73 (post-test). Students’ autonomy scores also improved from 3.4 to 4.6, with statistically significant differences (p < 0.05). In conclusion, formative assessment within scaffolded learning effectively enhances students’ writing competence and autonomy. This study implies that English lecturers should integrate formative assessment into scaffolded instruction to promote students’ independence and improve written communication skills.